Isolated large vessel pulmonary vasculitis leading to pulmonary artery aneurysm formation: a case report and literature review. (1st March 2018) - Moghaddam, Nima; Moghaddam, Bahar; Dehghan, Natasha; Brunner, Nathan W.
Abstract : Pulmonary artery (PA) vasculitis occurs in association with primary vasculitides—in particular, giant cell arteritis, Takayasu's arteritis, or Behçet's disease—or secondary vasculitis as a result of infections or malignancy. However, PA vasculitis in isolation and with concomitant aneurysmal dilation is an unusual finding. We present a rare case of PA aneurysm secondary to isolated PA vasculitis in an asymptomatic patient with no features of systemic vasculitis. This case highlights one of the first cases of PA vasculitis managed with surgical resection alone.